2020
DOI: 10.3389/fpsyg.2020.00646
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Surface and Underlying Forms When Processing Tonal Alternations in Mandarin Chinese: A Mismatch Negativity Study

Abstract: Phonological alternation (sound change depending on the phonological environment) poses challenges to spoken word recognition models. Mandarin Chinese T3 sandhi is such a phenomenon in which a tone 3 (T3) changes into a tone 2 (T2) when followed by another T3. In a mismatch negativity (MMN) study examining Mandarin Chinese T3 sandhi, participants passively listened to either a T2 word [tùu2 je4] /tùu2 je4/, a T3 word [tùu3 je4] /tùu3 je4/, a sandhi word [tùu2 jen3] /tùu3 jen3/, or a mix of T3 and sandhi word s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…These results suggest that tone 3 sandhi words in Mandarin are represented in their underlying T3-T3. This finds further support in an MMN experiment by Chien et al (2020), which showed that the presence of T3 sandhi in standards (disyllabic T3-T3 words) affected the occurrence of MMNs in monosyllabic T2 deviants, indicating that the underlying T3 exerts an influence in the passive listening of T3 sandhi words.…”
Section: The Effects Of Tone Sandhi Alternationsupporting
confidence: 59%
See 1 more Smart Citation
“…These results suggest that tone 3 sandhi words in Mandarin are represented in their underlying T3-T3. This finds further support in an MMN experiment by Chien et al (2020), which showed that the presence of T3 sandhi in standards (disyllabic T3-T3 words) affected the occurrence of MMNs in monosyllabic T2 deviants, indicating that the underlying T3 exerts an influence in the passive listening of T3 sandhi words.…”
Section: The Effects Of Tone Sandhi Alternationsupporting
confidence: 59%
“…Recent psycholinguistic and neurolinguistic studies have used different experimental tasks to further investigate the tonal representation of words undergoing tone sandhi in Mandarin Chinese (Chien et al, 2016;Chien, Yang, Fiorentino, & Sereno, 2020), Tianjin Chinese (Li, 2016), Taiwanese Southern Min (Chien, Sereno, & Zhang, 2017), and Shanghai Wu (Yan, Chien, & Zhang, 2020). These studies showed that the representation of the sandhi words accessed in word recognition is affected by a number of phonological properties of the tone sandhi pattern.…”
Section: The Effects Of Tone Sandhi Alternationmentioning
confidence: 99%
“…However, since T3 sandhi is a phonological alternation that occurs at the multisyllabic lexical level, it remains less clear whether these results obtained by using the pre-attentive EEG measure can account for the representation of lexical sequences. Chien et al (2020), to our knowledge, is the only study that used the oddball paradigm to probe the representation of disyllabic T3 sandhi words. In their study, four types of standard stimuli were constructed: a disyllabic T2-initial word /T2+T4/, a disyllabic T3-initial word /T3+T4/, a disyllabic sandhi word /T3+T3/ → [T2+T3], and a mixture of disyllabic sandhi and T3-initial words.…”
Section: Processing Sandhi In Different Morphological Processesmentioning
confidence: 99%
“…According to Chien et al (2020), the different MMN effects between the conditions T2+T4/T2 (standard/deviant) and T3+T3/T2 (standard/deviant) suggested that distinct neural mechanisms were required between processing the T2 standard words and the sandhi standard words. Moreover, Chien et al (2020) argued that the lack of the MMN effect in the sandhi condition could have two possible interpretations: (1) that the sandhi standard was not parsed as either a T2 or a T3 word; otherwise we should expect the similar MMN effects as observed in the T2 and the T3 word condition, or (2) that participants productively "rewrote" the initial sandhi syllable as well as the deviant T2 to an underlying T3, thereby no mismatched response was elicited in the sandhi standard condition. These two explanations proposed by Chien et al (2020) did not differentiate the underspecified and the canonical representation views specifically.…”
Section: Processing Sandhi In Different Morphological Processesmentioning
confidence: 99%
See 1 more Smart Citation